Оцінка технічного стану моторних масел за характеристичними показниками в процесі експлуатації двигунів сільськогосподарських машин - Панченко, Анатолій Іванович; Panchenko, Anatolii; Волошина, Анжела Анатоліївна; Voloshyna, Anzhela; Панченко, Ігор Анатолійович; Panchenko, Ihor; Лупинос, Герман Віталійович (Одеса : Видавничий дім “Гельветика”, 2024)
UA: У статті розглянуто проблему забезпечення надійності експлуатації двигунів внутрішнього згоряння сільськогосподарської техніки шляхом дослідження зміни якісних показників моторних масел у процесі їх роботи. Показано, що в умовах реальної експлуатації мобільних сільськогосподарських машин моторне масло зазнає інтенсивних фізико-хімічних перетворень, обумовлених дією високих температур і тисків, контактом з продуктами неповного згоряння палива, накопиченням механічних домішок і води, а також поступовим спрацьовуванням пакета присадок. В результаті цих процесів відбувається погіршення мастильних, протизносних та захисних властивостей олії, що негативно впливає на технічний стан та ресурс двигунів. Метою дослідження є встановлення закономірностей зміни характеристичних параметрів моторних масел залежно від напрацювання двигуна. У роботі використано експериментальну методику відбору та аналізу проб моторного масла з визначенням лужного і кислотного чисел, протизношувальних і протизадирних властивостей, в’язкісних характеристик та температури спалаху. Встановлено, що найбільш інформативними показниками технічного стану моторного масла є лужне число та протизношувальні властивості, граничні значення яких досягаються при напрацюванні 200–250 мотогодин. Обґрунтовано доцільність визначення строків заміни моторних масел за їх фактичним технічним станом, що дозволяє підвищити надійність експлуатації двигунів та знизити експлуатаційні витрати. /// EN: This article examines the problem of ensuring the reliable operation of internal combustion engines in agricultural machinery by studying changes in the quality parameters of motor oils during operation. It is shown that under real-life operating conditions of mobile agricultural machinery, motor oil undergoes intense physicochemical transformations caused by high temperatures and pressures, contact with incomplete combustion products, accumulation of mechanical impurities and water, and the gradual degradation of the additive package. These processes result in a deterioration in the lubricating, anti-wear, and protective properties of the oil, which negatively impacts the technical condition and service life of the engines. The aim of the study is to establish patterns in the changes in motor oil characteristics depending on the operating time of agricultural machinery engines and to substantiate informative rejection indicators that can be used to determine replacement intervals or the feasibility of oil regeneration. To achieve this goal, an experimental method was used, periodically collecting motor oil samples from engine crankcases, followed by determining its physicmechanical and service properties in accordance with current regulatory documents. The research assessed the base and acid numbers, kinematic viscosity, flash point, and the anti-wear and extreme pressure properties of the oil. The research revealed that the accumulation of mechanical impurities and water in engine oil after up to 300 engine hours does not reach maximum permissible values and cannot be used as a determining criterion for its ultimate state. It was shown that changes in kinematic viscosity and flash point are associated with fuel contamination of the engine oil; however, after the engine's thermal conditions stabilize, their values remain within acceptable limits. At the same time, it was established that the most informative indicators of the technical condition of engine oil are the base number and anti-wear properties, a decrease of more than 60% from the initial level observed after 200-250 engine hours, requiring the discontinuation of further oil use. The study substantiated the feasibility of switching from scheduled engine oil changes to changes based on their actual technical condition. The proposed approach allows for increasing the reliability of agricultural machinery engines, reducing the wear rate of their main components, and cutting operating costs.
Evaluation of the technical condition of motor oils based on characteristic indicators during operation of agricultural machinery engines
Keywords: моторне масло; бракувальний показник; протизадирні властивості; протизносні властивості; лужне число; кислотне число; характеристичні параметри; motor oil; rejection index; extreme pressure properties; antiwear properties; alkaline number; acid number; characteristic parameters